Morphological Forms Centered in Ibn Jinnī’s (392 AH) Discourse Strategy In His Book Al-Khasa'is (the Chapter of "the Convergence of Meanings Despite Differences in Roots and Structures"): The Principle of Subjectivity as an Example - Ahmad Ibrahim, Lect . Dr. Mohanad (Basra studies journal, 2026)
Discourse in Ibn Jinnī revolves around multiple forms of subjectivity, which the author presents within the context of linguistic argumentation in his book Al-Khaṣāʾiṣ, in the chapter entitled “On the Convergence of Meanings Despite the Diversity of Origins and Forms.” This is achieved through various linguistic techniques, the study being limited to one of these discourse techniques, namely the principle of subjectivity, which he embeds in certain morphological forms that he employs in his discourse. Keywords: morphological form, discourse strategy, Ibn Jinnī.